Characterization of a germline Vk gene encoding cationic anti-DNA antibody and role of receptor editing for development of the autoantibody in patients with systemic lupus erythematosus. - Suzuki, N; Harada, T; Mihara, S; Sakane, T (The Journal of Clinical Investigation, 1996)
We found previously that cationic anti-DNA autoantibodies (autoAbs) have nephritogenic potential and usage of a specific germline Vk gene, A30, has major influences on cationic charge of the autoAb in human lupus nephritis. In the present study, we have characterized A30 germline Vk gene using cosmid cloning technique in patients with SLE. A30 gene locus locates in less than 250 kb from the Ck region, and the cationic anti-DNA mRNA used the upstream Jk2 gene, indicating that cationic anti-DNA mRNA is a product of primary gene rearrangement. By using PCR technique, we found that A30 gene locus in the genome was defective in eight out of nine SLE patients without nephritis. In contrast, all nine patients with lupus nephritis had intact A30 gene. The presence and absence of A30 gene was associated with the development of lupus nephritis or not (P < 0.01, by Fisher's exact test, two-sided). It was thus suggested that absence of functional A30 gene may rescue from developing lupus nephritis in the patients. A30 is reported to be a potentially functional but rarely expressed Vk gene in humans. It is possible that normal B cells edit primarily rearranged A30 gene with autoreactive potentials by receptor editing mechanism for changing the affinity of the B cell Ag receptor to avoid self-reactivity, whereas SLE B cells may have a defect in this mechanism. Indeed, we found that normal B cells edit A30-Jk2 gene in their genome possibly by inversion mechanism, whereas SLE B cells contain rearranged A30-Jk2-Ck gene in the genome and express A30-associated mRNA, suggesting that receptor editing mechanism is also defective in patients with SLE. Our study suggests that polymorphism of Ig Vk locus, and failure of receptor editing may contribute to the development of pathogenic anti-DNA responses in humans.